2019
DOI: 10.14233/ajchem.2020.22177
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Components of Agarwood (Aquilaria crassna) Essential Oils Grown in Various Regions of Asia

Abstract: This study presents a chemometric study on agarwood (Aquilaria crassna) essential oils extracted from selected agarwood samples grown in various regions of Asia. Adopting gas chromatography-mass spectrometry (GC-MS) technique, it was revealed that essential oils, produced by hydrodistillation,constitutes mainly volatile aromatic compounds. Several major components are shared in all samples including dihydro-agarofuran-15-al, jinkoeremol, 10-epi-γ-eudesmol, agarospirol, valerianol, n-hexadecanoic acid, neopetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The composition and content of essential oils depend on the species, extraction method, and soil of each region. For example, Marie-Laure Lota et al 9 The content of essential oils from varieties grown in France with higher levels of limonene, α-Pinene, Myrcene, and Sabinene than before (52.2-96.2%, 0.1-2, 1%, 1.3-1.8%, 0.1-1.3%, respectively). Gulay Kirbaslar et al 30 announced the composition of tangerine peel oil grown in Turkey obtained 45 compounds, of which, limonene (90.7%), followed by myrcene (2.1%), and α-pinene (0.5%).…”
Section: Results Analysis Of Gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and content of essential oils depend on the species, extraction method, and soil of each region. For example, Marie-Laure Lota et al 9 The content of essential oils from varieties grown in France with higher levels of limonene, α-Pinene, Myrcene, and Sabinene than before (52.2-96.2%, 0.1-2, 1%, 1.3-1.8%, 0.1-1.3%, respectively). Gulay Kirbaslar et al 30 announced the composition of tangerine peel oil grown in Turkey obtained 45 compounds, of which, limonene (90.7%), followed by myrcene (2.1%), and α-pinene (0.5%).…”
Section: Results Analysis Of Gc-msmentioning
confidence: 99%
“…Nowadays, fragrant compounds derived from nature are gaining great attention and becoming a trend, thus research on them is growing continuously [6][7][8][9] . Through previous studies and consumption practice, it has been shown that when using products of plant origin brings great effects with less toxicity and side effects.…”
Section: Introductionmentioning
confidence: 99%